Shore Seines of Visakhapatnam in the East Coast of India - G., Rajeswari; R., Raghu Prakash (Fishery Technology, 2025)
The Shore seines are traditional gears used to exploit the inshore fishery along East Coast of Andhra Pradesh. This gear varies in their construction and mode of operation from one region to another. Two types of seines are operated along the Visakhapatnam Coast. The seines operated without cod end are locally called as Alivi vala. The Seines operated with cod end are called Pedda vala. The paper gives technical details of the two types of shore seines, its design, materials used, method of fabrication and operation.